2015
DOI: 10.1175/bams-d-13-00169.1
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Emerging Local Anthropogenic Emissions in the Arctic Region: The ACCESS Aircraft Campaign Experiment

Abstract: International audienceArctic sea ice has decreased dramatically in the past few decades and the Arctic is increasingly open to transit shipping and natural resource extraction. However, large knowledge gaps exist regarding composition and impacts of emissions associated with these activities. Arctic hydrocarbon extraction is currently under development due to the large oil/gas reserves in the region. Transit shipping through the Arctic as an alternative to the traditional shipping routes is currently underway.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(78 citation statements)
references
References 96 publications
2
76
0
Order By: Relevance
“…Examples are ACCESS (Roiger et al, 2014) and POLARCAT/POLMIP (Emmons et al, 2015). Note that MACC is providing support to flight planning during field campaigns like ACCESS.…”
Section: Case Studiesmentioning
confidence: 99%
“…Examples are ACCESS (Roiger et al, 2014) and POLARCAT/POLMIP (Emmons et al, 2015). Note that MACC is providing support to flight planning during field campaigns like ACCESS.…”
Section: Case Studiesmentioning
confidence: 99%
“…An overview of the ACCESS aircraft campaign is given in Roiger et al (2015). For completeness, we briefly describe the details of the ACCESS campaign, conducted in July 2012 using the DLR Falcon-20 aircraft based in northern Norway.…”
Section: Access Campaignmentioning
confidence: 99%
“…The main aim was to collect data on emerging local pollution sources in the Arctic in order to evaluate their impacts on atmospheric composition and on regional air quality and climate. During the campaign, emissions from shipping and oil/gas extraction, as well as pollution plumes transported from metal smelting activities in north-west Russia and from Siberian fires were studied (see Roiger et al, 2015 for further discussion). An analysis of ACCESS flights focusing on ship emissions and their impacts can be found in Marelle et al (2016).…”
Section: Access Campaignmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies (Roiger et al, 2015;Law et al, 2014;Stohl et al, 2013, and references therein) have shown that a number of other factors, overlooked or underestimated in previous climate modeling, should be taken into consideration. Primarily, there had been an accelerated development of northern territories, associated with extraction and processing of mineral resources, combustion of petroleum gas in the regions of oil and gas production, and intensification of sea and air transportation.…”
Section: S M Sakerin Et Al: On Measurements Of Aerosol-gas Composimentioning
confidence: 99%